First report of the male of Zamora granulata Roewer, 1928, with implications on the higher taxonomy of the Zamorinae Kury, 1997 (Opiliones, Laniatores, Cranaidae) - Kury, Adriano B. (Zootaxa, 2012)
Males of Zamora granulata Roewer, 1928—a species known from Zamora, Ecuador—are reported for the first time. Thestudy of this species, especially the male genitalia, along with all species of Zamorinae Kury, 1997, allowed to reach thefollowing conclusions: 1) Zamora vulcana Kury, 1997, from Cotopaxi, Ecuador, does not belong to Zamora and istransferred to Rivetinus Roewer, 1914; 2) Zamora granulata, the name-bearer of Zamorinae, is not an Agoristenidae andtherefore Zamorinae is placed in Cranaidae; 3) Zamorinae is redefined based on previously unavailable information frommale genitalia; (4) some genera hitherto placed in Zamorinae which present a combination of a generalized gonyleptoidhabitus plus an agoristenid genitalia (which includes Globibunus Roewer, 1912 and Rivetinus), are placed in Globibuninaesubfam. nov. Based on the examination of the holotype of Prostygnus vestitus Roewer, 1913 (from Ecuador, notColombia, nor Venezuela), and new material of Cutervolus albopunctatus Roewer, 1957, the Prostygninae are restrictedto Cutervolus Roewer, 1957 and Prostygnus Roewer, 1913, with distribution accordingly restricted to southern Ecuadorand northern Peru. Iconographic complements are made on the type species of these two genera, and their male genitaliaare illustrated for the first time. All other Prostygninae are considered Gonyleptoidea incertae sedis. Emended diagnoses are provided for Globibuninae, Prostygninae and Zamorinae.